EFEK SITOTOKSIK KOMBINASI EKSTRAK METANOL DAUN KENIKIR (Cosmos caudatus, Kunth) DAN DOKSORUBISIN TERHADAP SEL KANKER PAYUDARA T47D SECARA IN-VITRO DAN IN-SILICO - Fera Elia Fita; Dewi Listianingsih; Yunita Ayu Hapsari; Raka Galih Pradana; Erika Indah Safitri; Ibrahim Arifin (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACTDoxorubicin is chemotherapeutic agents used widely for breast cancer therapy. The use of doxorubicin may cause cardio toxicity and multi-drug resistance. In order to overcome this side effect, a combined therapy using the methanol extracts of kenikir leaves is developed. The purposes of this study are to measure the cytotoxic effect of methanol extracts of kenikir leaves and doxorubicin combination treatment against T47D breast cancer cell growth in-vitro and in-silico, as well as determining the optimal dose combination that produces the most potent cytotoxic effects. The extraction of kenikir leaves is performed with soxhletation method. The cytotoxicity assay on the T47D breast cancer cells is carried out using MTT assay. The result of this research shows that the value of IC50 methanol extracts of kenikir leaves is 778.05μg/mL. The treatment of the methanol extracts of kenikir leaves and doxorubicin combination treatment results in a strong synergy at the concentration 130 μg/mL (-41 nM); 195 μg/mL (-41 nM) and 130 μg/mL (-27.33 nM) with the value of Combination Index 0.2; 0.3 and 0.3 respectively. The result of in-silico test shows that the bond energies of aglycone flavonoid and quercetin glycoside on Bcl-2 are -63.3359 and -67.0414. Key words: Kenikir leaves extract, doxorubicin, T47D cells, molecular docking